Ta’tsiiru Thariiqati SAVI ‘ala Tarqiati Nataiju Ta’allum Al-Lughah Al-‘Arabiyah - Jamaluddin, J Nurhawani (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2025)
The researcher noted that the students' ability is weak and their scores are less than 60, which is a deficiency from the score decided by the institution, unlike others who made an effort in learning and obtained a score of more than 75. The aim of this research is to highlight the effect of SAVI method of improving Scores of Arabic Language Learningamong first-graders at Mahad Darul Ulum. The population in this research is all 63 students in first grade of Mahad Darul Ulum.. The sampling technique used in this research was purposive sampling. The sample will consist of two classes of 42 students, one class will be an experimental class using the SAVI method and the other class will be a control class whose learning will use the Muhadharah method. The research method used is quantitative with a quasi-experimental design. The method of data collection is pre-test and post-testing. The data obtained by the research were processed in the form of statistical analysis. The research results of this research are that the use of the SAVI method greatly affects the promotion Arabic language learning among seventh grade students in Mahad Darul Ulum.. The result appeared 64.76 in the muhadharah method and the average value of the subsequent test in the experimental group using the SAVI method 85.48, so there were significant differences in the learning scores of Arabic between the experimental groups and the control groups. Thus, the SAVI method has an effect on the improving scores of Arabic language learning.